Patient and caregiver perceptions of communication of prognosis in high grade glioma - Lobb, Elizabeth; Halkett, Georgia; Nowak, A. (Springer New York LLC, 2011)
This study sought the views of patients and their caregivers on their experience of being diagnosed with high grade glioma. Purposive sampling was used to recruit 19 patients and 21 caregivers from the medical oncology unit of a tertiary hospital. A semi-structured face-to-face interview was conducted. Interviews were audiotaped and transcribed verbatim. Data was analysed based on Grounded Theory and using the constant comparison method. This paper focuses on patient and carer perceptions of the initial communication about the diagnosis of high grade glioma and its prognosis. Themes identified included: (a) shock at hearing the diagnosis; (b) trying to understand and process prognostic information when still in shock; (c) the perception of hope being taken away; (d) individualizing prognostic information; and (e) clinicians’ lack of communication skills. This study shows that the first communication of prognosis to patients with high grade glioma and their caregivers requires careful negotiation. It illustrates the inability of individuals to process detailed prognostic information when in a state of initial shock and distress. The importance of balancing honesty with hope in the communication of a poor prognosis is highlighted. We recommend that clinicians seek patient preferences for the amount and type of information they require and that prognostic information be individualized. Detailed discussions of prognosis should only take place with senior medical staff, or advanced trainees who have demonstrated acceptable communication skills.